Work-Life Balance and Time Flexibility of Female Employees in the Home Industry: A Systematic Literature Review - Telly Pauline Ulviana Siwi; Debi Septiani; Yike Diana Putri; Agung Indriansyah (CV Edujavare Publishing, 2026)
Home-based food industries, such as the traditional